Interferensi Fonologis Bahasa Sunda oleh Penutur Asing di Akun Tiktok @Dmitrii - Herdiyanti, Febri; Taufiqurrohman, Moh. Rizqi; Maulida, Rahma Noor; Nurhalisa, Windiana; Dakir, Siti Humaira Ramadhani; Mahardika, Muhammad Desta; Widyastuti, Temmy (Lingua Susastra, 2025)
This study examines the phenomenon of Sundanese phonological interference by foreign speakers on the social media platform TikTok, particularly on the @Dmitrii account.  The background of this study stems from the increase in language interaction due to globalization, which has given rise to influences in various communication contexts, including regional languages such as Sundanese. The purpose of this study is to explain the forms of phonological errors found in the speech of foreign speakers and to determine the factors that cause them. The method used is descriptive qualitative with listening and note-taking techniques. The data used in this study were sourced from 40 TikTok videos from @Dmitrii that contained elements of Sundanese. The researcher found 168 phonological errors, including 68 phoneme additions, 48 phoneme omissions, and 52 phoneme sound changes that did not comply with Sundanese phonological rules. The factors causing interference included internal factors (the influence of the mother tongue, limited Sundanese language skills, and differences in phonological systems) and external factors (a bilingual environment, digital communication style, and lack of exposure to native Sundanese speakers). This phenomenon proves that phonological interference is not only an error but also a natural process of phonetic adaptation in learning a second language.